2017
DOI: 10.4172/2329-6836.1000251
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Evaluation and DNA Binding Ability of Catalytically Synthesized New Steroidal Lactones

Abstract: In an attempt to find a new class of cytotoxic agents, a series of fused steroidal derivatives containing lactone moiety were prepared via Michael addition reaction of α, β-unsaturated steroidal ketones with ethyl chloroacetate in basic medium. The characterization of novel compounds was accomplished by spectroscopic techniques such as IR, 1 H NMR, 13 C NMR, Mass spectrometry and elemental analysis. The compounds were screened for in vitro cytotoxicity against some particular human cancer cell lines using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Mashrai et al studied the DNA binding ability of synthesized steroidal lactones. [12] It was seen that cytotoxicity experiments (MTT assay) of the steroidal lactones have been identified showing potential anticancer behavior of IC 50 = 19.27 against the MCF-7 cell line. Elaine et al reported antileukemic properties of sesquiterpene lactones.…”
Section: Dna Cleavagementioning
confidence: 99%
“…Mashrai et al studied the DNA binding ability of synthesized steroidal lactones. [12] It was seen that cytotoxicity experiments (MTT assay) of the steroidal lactones have been identified showing potential anticancer behavior of IC 50 = 19.27 against the MCF-7 cell line. Elaine et al reported antileukemic properties of sesquiterpene lactones.…”
Section: Dna Cleavagementioning
confidence: 99%